Delineating Ababi Mountains spring recharge zones using combined isotope hydrology and geophysical methods - I Nengah Simpen; I Wayan Redana; Putu Doddy Heka Ardana (Journal of Water and Land Development)
Sustainable groundwater management requires accurate identification of spring recharge zones, particularly in volcanic regions where water resources are critical. This study aimed to delineate the groundwater recharge zone of the Ababi Spring in Bali’s Karangasem Regency by integrating isotope hydrological and geophysical techniques. Water samples were collected from five locations (211–978 m a.s.l.) and analysed for stable isotopes (δ2H or δD and δ18O). Vertical electrical sounding and audio magnetotelluric surveys were conducted to validate findings and map subsurface structures. The local meteoric water line was established (δ2H = 4.4912δ18O + 7.1419) and an isotope-elevation relationship was developed. The spring water exhibited depleted isotopic values (δ18O: −7.706‰, δ2H: −39.748‰) compared to local precipitation, indicating a higher-altitude source. The analysis identified the recharge zone at approximately 2,118 m a.s.l. Geophysical surveys revealed subsurface structures connecting the recharge area to the spring, with resistivity patterns indicating preferential flow paths going through fractured volcanic rocks. The effectiveness of this integrated approach was further validated through additional isotopic analysis of rainfall at 1,514 m a.s.l. This supported the established isotope-elevation relationship model (R2 = 0.6847). The study demonstrates the value of combining hydrochemical and geophysical methods for accurate recharge zone delineation in a volcanic terrain, particularly in regions with complex hydrogeological settings. These findings provide crucial information for implementing targeted conservation strategies and ensuring sustainable water resource management in the Karangasem region, while establishing a methodological framework applicable to similar volcanic environments.